Los documentos de gestión para la Comisión de Regantes Sausal - Caballero Arana, Eduardo Efraín (2011)
This thesis focuses on formulating and proposing Records Management for implementation in the Sausal Irrigation Commission, since these instruments are important for good performance inside the organization, as is any guide, control and support to assist Commission optimize the operation of staff and reducing the risk of dysfunction that may occur within it, and thus contribute to the successful development of the same Development of this research derives from a thorough study of the inside of the Organization under inductive and deductive methods, analytic-synthetic, statistical and survey techniques and simple observation. You took into account a methodology and theoretical framework to guide the formulation of management documents which explains all the tools used for diagnosis, analysis and proposal of such documents. Users of Sausal Irrigation Commission, said they agreed to improve the current organization, so as to meet the goals and institutional objectives and improve the quality of customer service. The proposed management administrative documents provide great supports to achieve effective management, among them are: the Rules of Organization and Functions (ROF), Table Allocation of Personnel (CAP), the Organization and Functions Manual (MOF), Regulations Internal Staff (RIP), and an adequate organizational design in the Sausal Irrigation Commission